2023
DOI: 10.1200/jco.22.00575
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab Deruxtecan in Anti–Human Epidermal Growth Factor Receptor 2 Treatment–Naive Patients With Human Epidermal Growth Factor Receptor 2–Low Gastric or Gastroesophageal Junction Adenocarcinoma: Exploratory Cohort Results in a Phase II Trial

Abstract: PURPOSE To investigate efficacy and safety of trastuzumab deruxtecan (T-DXd) in human epidermal growth factor receptor 2 (HER2)–low gastric or gastroesophageal junction (GEJ) adenocarcinoma. METHODS Patients with locally advanced or metastatic HER2-low (cohort 1, immunohistochemistry 2+/in situ hybridization–negative; cohort 2, immunohistochemistry 1+) gastric/GEJ adenocarcinoma treated with at least two prior regimens, including fluoropyrimidine and platinum, but anti-HER2 therapy naive, received T-DXd 6.4 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 22 publications
3
30
0
1
Order By: Relevance
“…There were no drug-related TEAEs associated with death. Safety results in the exploratory HER2-low cohorts were consistent with those of the primary cohort, and overall, T-DXd demonstrated a manageable safety profile [35] .…”
Section: Anti-her2 Antibody-drug Conjugatesupporting
confidence: 57%
See 1 more Smart Citation
“…There were no drug-related TEAEs associated with death. Safety results in the exploratory HER2-low cohorts were consistent with those of the primary cohort, and overall, T-DXd demonstrated a manageable safety profile [35] .…”
Section: Anti-her2 Antibody-drug Conjugatesupporting
confidence: 57%
“…The experimental results showed that the objective response rate (ORR) of cohort 1 was 26.3%, and the median progression-free survival (mPFS) and mOS were 4.4 and 7.8 months, respectively [34] . The ORR of cohort 2 was 9.5%, and the mPFS and mOS were 2.8 and 8.5 months [35] . 70.0% of patients in cohort 1 and 79.2% in cohort 2 had treatment-emergent adverse events (TEAEs) of grade 3 or higher.…”
Section: Anti-her2 Antibody-drug Conjugatementioning
confidence: 88%
“…In BC, the quantum seems beyond what can be reliably discerned with IHC, 1 but in gastric cancer, such a quantum seems to be consistently identifiable with IHC. 2 As ADCs are moving their development toward IHC-based agnostic indications, to us, this should be taken cum grano salis. Current evidence suggests no universal generalizability-albeit histology per se may not be the ultimate determinant of the response patterns, but unidentified molecular determinants.…”
Section: Oncogene Addiction Antigen Expression and Spatial Distributi...mentioning
confidence: 99%
“…In breast cancer (BC), T-DXd outperforms standard chemotherapy in both ERBB2 -amplified and ERBB2-low tumors, irrespective of ERBB2 immunohistochemistry (IHC) expression . However, in gastric cancer, a climax of objective responses (objective response rate [ORR]) is observed according to the ERBB2 IHC score: ORR appears higher in patients with ERBB2 IHC score 3+ gastric cancer (52.8%) than ERBB2 IHC score 2+ gastric cancer (28.6%), with lowest rates in ERBB2-low (ORR in ERBB2 IHC score 1+ gastric cancer: 9.5%), corresponding to a median progression-free survival (PFS) of only 2.8 months . Possibly, the dose-effect relationship retains some disease specificity, with a minimum quantity of antigen expression (a quantum) triggering the activity.…”
Section: Oncogene Addiction Antigen Expression and Spatial Distributi...mentioning
confidence: 99%
“…81 The trial randomized 187 heavily pretreated patients with metastatic HER2 expressed GEA to receive 2: Subsequently, the HER2-low cohort results were published. 82 The trial included 21 patients with HER2 2+/FISH negative tumours (cohort 1) and 24 patients with HER2 1+ tumours (cohort 2); those patients were naive to anti-HER2 treatment as per international guidelines 5 and received T-Dxd as ⩾third-line treatment. There was an ORR of 26.3% and 9.5% for the experimental arm in cohorts 1 and 2, respectively; also, in this case, major responses were recorded (partial responses in 5 and 2 patients, respectively).…”
Section: Therapeutic Advances In Medical Oncologymentioning
confidence: 99%